The Effect of Service Quality, Trust and Customer Satisfaction on Customer Loyalty in Online Shopping Applications - Andini Dalimunthe, Nurul; Nefianto, Tirton (Lafadz Jaya Publisher, 2025)
Service quality an important crucial role in marketing strategies that online shopping app companies can implement by providing the best facilities for their users to foster trust and satisfaction, leading to consumer loyalty. This study aimed to determine the greatest influence on customer loyalty. This quantitative study employed a purposive sampling technique, distributed through questionnaires to 170 online shopping app users aged 17–65 years in the Greater Jakarta area. Primary data analysis was conducted using the Structural Equation Modeling (SEM) method. The results of this study indicate that service quality does not impact customer loyalty. Service quality impacts customer satisfaction and trust, while trust impacts customer satisfaction. Customer satisfaction impacts customer loyalty. Trust has the greatest direct influence on customer satisfaction. This study contributes to online shopping app companies in maintaining and improving service quality, which can be seen from several factors formed from each consumer complaint in an optimal and measurable manner. For further research, the researcher suggests expanding the research area and seeking objects in other fields.